PENGARUH INSTAGRAM TERHADAP PREFERENSI POLITIK MAHASISWA UNIVERSITAS SYIAH KUALA PADA PEMILU 2024 - Salsabila, Aura; Hasan, Effendi; Ahmady, Iqbal (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2025)
This study aims to examine the extent to which Instagram news coverage influences the political preferences of presidential candidates among students at Syiah Kuala University. As a popular social media platform among the younger generation, Instagram holds significant potential in shaping public opinion through visual and narrative content. The study adopts the agenda-setting theory, which posits that the media has the power to shape which issues are considered important by the public. A descriptive quantitative method was employed to explore the relationship between variables. The validity test results show that all indicators of variables X and Y are valid, with calculated r-values greater than the critical r-table value at a significance level of 0.05. This indicates that Instagram coverage influences students political preferences, thereby supporting McCombs and Shaw's agenda-setting theory. However, the analysis of statement number 12 reveals that a majority of respondents (39.6%) disagreed that social media campaigns significantly influence their voting decisions, while 34.2% agreed, and 26.2% remained neutral. These findings suggest that although social media is capable of shaping public opinion, its influence on individual political decisions remains limited.